DFT Study on Redox-Switchable Second-Order Nonlinear Optical Properties of η5-Monocyclopentadienyliron(II) and Ruthenium(II) Complexes with Benzo[c]thiophene Nitrile Ligand - Mendes, Paulo J. (2013)
Density functional theory (DFT) has been carried out to investigate the switching of the second-order nonlinear optical (NLO) properties of η5-monocyclopentadienyliron(II) and ruthenium(II) model complexes presenting 5-(3-(thiophen-2-yl)benzo[c]thiophen-1-yl)thiophene-2-carbonitrile as a ligand. The switching properties were induced by redox means. Both oxidation and reduction stimulus have been considered and calculations have been performed both for the complexes and for the free benzo[c]thiophene derivative ligand in order to elucidate the role played by the organometallic fragment on the second-order NLO properties of these complexes. B3LYP, CAM-B3LYP and M06 functionals were used for our calculations. The results show some important structural changes upon oxidation/reduction that are accompanied by significant differences on the corresponding second-order NLO properties. TD-DFT calculations show that these differences on the second-order NLO response upon oxidation/reduction are due to a change in the charge transfer pattern, in which the organometallic iron and ruthenium moieties play an important role. The calculated static hyperpolarizabilities were found to be strongly functional-dependent. CAM-B3LYP, however, seems to predict more reliable structural and optical data as well as hyperpolarizabilities when compared to experimental data. The use of this functional predicts that the studied complexes can be viewed as acting as redox second-order NLO switches, in particular using oxidation stimulus. The βtot value of one-electron oxidized species is at least ∼ 8.3 (for Ru complex) and ∼ 5.5 times (for Fe complex) as large as that of its non-oxidized counterparts.